Communication in selected Eastern Cape public healthcare facilities offering termination of pregnancy services: inter/intra-cultural implications - Mavuso, Snethemba Fikile (Rhodes University, Faculty of Humanities, School of Languages, 2017)
This study examines pre-termination of pregnancy (PTOP) counselling, focussing on issues of language and access, and sociocultural influences. This research examines linguistic and cultural aspects of communication between healthcare providers and clients in PTOP contexts. The overarching aim of this research was to identify patterns that indicate miscommunication and to propose ways to bridge any linguistic and cultural gaps. This research examine how social norms related to turn taking guide healthcare providers - clients interaction and how the clients respond to advice offered during the counselling sessions. The study provides an indepth understanding of linguistic and cultural barriers in public healthcare, and further emphasizes the need for implementation of support systems for cross-cultural and effective patient-centred communication in healthcare. The findings in this study are thatpresent that miscommunication occurs within intercultural and intra-cultural medical encounters. Excessive use of medical terminology causes communication difficulties. Clients often provide a positive response to indicate that they understand what the healthcare provider is communicating. Clients sometimes respond positively out of politeness. This practice is common in some cultures; it often occurs when the recipient is interacting with a figure of authority or someone of higher positioning. It is found that healthcare provider's value systems sometimes have an impact on their professional conduct, influencing the type of PTOP counselling provided to clients. Sometimes the language and communication barriers have a negative impact on the quality of care/PTOP counselling. This study argues that healthcare provider's communication styles and value systems influence PTOP counselling. Healthcare providers have the power to control the medical discourse; their turns at talk influence those of clients. The manner in which the nurses and counsellors address the clients elicits a certain response. This study thus suggests that healthcare providers need to improve their communicative skills, be mindful of their position as power holders and adopt a patient-centred approach, which is crucial for clinical and cultural competence.
Keywords: Communication in medicine -- South Africa; Medical care -- Communication systems -- South Africa